Non-pharmacological interventions for restless legs syndrome: a systematic review of randomised controlled trials. Issue 17 (14th August 2019) - Harrison, Eloise G.; Keating, Jennifer L.; Morgan, Prue E.
Abstract: Introduction: Restless legs syndrome (RLS) is a sensorimotor disorder characterised by an uncomfortable urge to move the legs. Management is primarily pharmacological. Effects for non-pharmacological, non-surgical options are published but lack systematic examination. Objectives: To synthesise results of non-pharmacological/non-surgical treatment compared to no-treatment controls or alternative treatment for RLS on any relevant outcome. Methods: Databases and reference lists of reviews were searched for randomised controlled trials (RCTs) comparing non-pharmacological treatment to alternative or no treatment controls for idiopathic RLS. Search results were independently screened for inclusion by two researchers; disagreements regarding eligibility were resolved with discussion. Outcomes were summarised, and pooled where possible in meta-analysis. Results: The search yielded 442 articles. Eleven trials met inclusion criteria. Repetitive transcranial magnetic stimulation, exercise, compression devices, counterstrain manipulation, infrared therapy, and standard acupuncture were significantly more effective for RLS severity than control conditions. Vibration pads, cryotherapy, and transcranial direct current stimulation were ineffective in reducing RLS severity. Vibration pads, cryotherapy, yoga, compression devices, and acupuncture significantly improved some sleep-related outcomes. Conclusions: Few studies were identified and quality of evidence was not high. Some non-pharmacological interventions may be beneficial for reducing RLS severity and enhancing sleep. Implications for Rehabilitation: The current management of restless leg syndrome is primarily pharmacological, and medications can have unwanted side effects. Repetitive transcranial magnetic stimulation, exercise, compression devices, counterstrain manipulation, infrared therapy, and standard acupuncture may reduce restless leg syndrome severity. Vibration pads, cryotherapy, yoga, compression devices, and acupuncture may improve some sleep-related outcomes in restless leg syndrome. Non-pharmacological interventions for RLS may cause placebo effects and rehabilitation professionals should control for this possibility in future investigations.